Isolation and identification of thermophilic amylolytic bacteria from Likupang Marine Hydrothermal, North Sulawesi, Indonesia - Elvy Like Ginting; Letha Wantania; Emma Mauren Moko; Reiny Tumbol; Mayse Siby; Stenly Wullur (Society for Indonesian Biodiversity, 2021)
Abstract. Ginting EL, Wantania LL, Moko EM, Tumbol RA, Siby MS, Wulur S. 2021. Isolation and identification of thermophilic amylolytic bacteria from Likupang Marine Hydrothermal, North Sulawesi, Indonesia. Biodiversitas 22: 3326-3332. The aims of the research were to isolate and identify the amylase-producing thermophilic bacteria from Likupang Marine Hydrothermal, North Sulawesi, Indonesia. The bacteria were characterized based on the colony and cell morphology and subsequently screened for their amylase activities. The bacterial isolates were identified based on 16S rRNA gene sequences. There were 12 thermophilic bacteria isolates from Likupang Marine Hydrothermal that were able to produce amylase. Two selected isolates (L3 and L9) had an amylolytic index value in the range of 3.04-3.52 at 55oC. The colonies of L3 and L9 are circular, and they are Gram positive, rod-shaped, and motile bacteria. Based on the 16S rRNA gene sequences and phylogenetic tree analysis showed that L3 was closely related to Bacillus caldotenax with 93% similarity while L9 had 99% similarity to B. caldotenax. Hence, we identified L3 isolate as Bacillus sp. strain L3 and L9 isolate as B. caldotenax strain L9. Both of these bacteria were grouped as Geobacillus thermoleovorans.